2020
DOI: 10.1021/acs.jpcc.0c03862
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer from Organic Molecules to Molybdenum Disulfide: Influence of the Fluorination of Iron Phthalocyanine

Abstract: Layered transition metal dichalcogenides (TMDCs), such as molybdenum disulfide (MoS2), are currently in the focus of interest due to their novel electronic properties. The adsorption of molecules is a promising way to tune the electronic structure of TMDCs. We study interface properties between MoS2 and differently fluorinated iron phthalocyanines (FePcF x , x = 0, 4, 16) using X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), angle-resolved photoelectron spectroscopy (ARPES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 77 publications
3
40
1
Order By: Relevance
“…5 In another example, angle-resolved photoelectron spectroscopy (ARPES) has shown that iron phthalocyanine (FePc) hybridizes with MoS 2 near the Κ point (Figure 2c,d). 6 While it is known that hybridization with organic adlayers can influence the band structure of 2D materials, the fundamental limit of this effect remains unknown. To develop and verify chemical intuition about this topic, systematic DFT and ARPES studies of a wide variety of organic−2D heterojunctions are needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 In another example, angle-resolved photoelectron spectroscopy (ARPES) has shown that iron phthalocyanine (FePc) hybridizes with MoS 2 near the Κ point (Figure 2c,d). 6 While it is known that hybridization with organic adlayers can influence the band structure of 2D materials, the fundamental limit of this effect remains unknown. To develop and verify chemical intuition about this topic, systematic DFT and ARPES studies of a wide variety of organic−2D heterojunctions are needed.…”
mentioning
confidence: 99%
“…Copyright 2020 Wiley-VCH. (c and d) Reprinted with permission from ref . Copyright 2020 American Chemical Society.…”
mentioning
confidence: 99%
“…The IP value determines the work-function potential, and the difference between the vacuum potential is equal to the HOMO level of the materials; we therefore used UPS to measure the IP values of catalyst molecules and the prepared catalysts (see the Supporting Information, S5). …”
Section: Results and Discussionmentioning
confidence: 99%
“…To gain further information about the molecular orientation of CoPc on HBC/Au(111) as a function of the film thickness, polarization-dependent X-ray absorption spectra at the N-K edge were taken for CoPc/HBC/Au(111). N 1s π*-excitations can be used in a similar manner to C 1s π*-excitations for the analysis of the molecular orientation of TMPcs. , For CoPc on HBC, C 1s π*-excitations are in superposition with HBC-related transitions and cannot be used for the determination of the orientation. In Figure , polarization-dependent N-K edge spectra for a 0.3 nm CoPc layer (about one ML) and a thin film of 1.5 nm thickness are shown for the two prominent angles corresponding to grazing (θ = 10°) and normal (θ = 90°) incidence of the incoming p-polarized synchrotron light.…”
Section: Resultsmentioning
confidence: 99%